MORPHOLOGICAL CHARACTERIZATION AND MOLECULAR PHYLOGENY OF COLLETOTRICHUM CAPSICI CAUSING LEAF SPOT DISEASE OF TURMERIC - ADHIPATHI, PASUVARAJI; NAKKEERAN , SEVUGAPERUMAL; CHANDRASEKARAN, ANGANNAN (The Bioscan, 2013)
Leaf spot disease is one of the major economic constraint which hampers turmeric production. Twenty isolates of Colletotrichum capsici causing leaf spot of turmeric were evaluated for their morphological, pathogenic, virulence and genetic characterization using random amplified polymorphic DNA (RAPD-PCR). The isolates were categorized into seven groups, based on the morphological characteristics, produced cottony colonies with zigzag to ring or circular pattern of growth. However, differences were obtained in colony colour, shape and size of conidia. Isolates were classified into four groups designated as highly resistant, moderately resistant, moderately sensitive and highly sensitive group based on the effect of propiconzole. The 5.8 S rDNA of ITS region was amplified which confirmed the specific amplicon size of 590 bp. The molecular polymorphism among isolates were analysed by means of RAPD-PCR and the genetic coefficient matrix derived from the scores of RAPD profile showed that minimum and maximum per cent similarities among isolates were in the range of 70 to 96 percent respectively. The cluster analysis by unweighted pair-group method with arithmetic average (UPGMA), separated the isolates into four clusters which confirming the genetic diversity among isolates. However, morphological, virulence and RAPD grouping of isolates suggested no correlation among the test isolates.